Confidentiality and disclosure concerns across scholarly disciplines: a mini-review - Subarimaniam, Neerushah; Zakaria, Noor Syamilah (Human Resource Management Academic Research Society, 2019)
Confidentiality and disclosure remain a significant concern regardless of age, gender, race, religion, national origin, and social class. Confidentiality reflects the act of keeping secret and protecting the privacy of clients. On the other hand, disclosure reflects the act of sharing matters with others. The thought about ‘to tell or not to tell’ exists in every individual especially when the individual share issues with the other person. Some choose to disclose and some choose to restrict disclosure. Thus, the aim of this mini-review is to discuss various concerns about confidentiality and disclosure across multiple scholarly disciplines. Furthermore, the review would provide comparisons between the need to protect confidentiality and the need to disclose. An electronic database was used to retrieve comprehensive literature. A number of articles were evaluated and the mini-review involved multiple disciplines. The methodology began with the designation of a search strategy, data filtration, in-depth filtration involving inclusion and exclusion criteria, and production of final output. We conclude that most of the findings highlight the need to protect clients’ confidentiality and control disclosure whereas the rest of the findings discussed the need for disclosure. In short, the mini-review highlights that confidentiality is an ethical duty.